Steinernema pui sp. n. (Rhabditida, Steinernematidae), a new entomopathogenic nematode from Yunnan, China - Qiu, Lihong; Zhao, Jingxiu; Wu, Zhongdao; Lv, Zhiyue; Pang, Yi (Zootaxa, 2011)
A new species of entomopathogenic nematode, herein described as Steinernema pui sp. n. was recovered from a soil sample collected from Xiao-jie town, Jing-hong city, Xi-shuang-ban-na district in Yunnan province, the People’s Republic of China in December 2002. Both morphological and molecular evidence show congruently that S. pui sp. n. belongs to the S. glaseri group. It can be separated from all described Steinernema species by a combination of morphological and morphometrical characters of adult and juvenile stages, including spicule and gubernaculum shape of the first generation males (spicule bearing an aperture on the tip and an irregular-shaped concave on ventral side of the lamina close to the tip; gubernaculum with a short needle-shaped cuneus); the tail and vulva shape of the first generation females (tail conoid and pointed with a mucron; vulva with a short double flapped epiptygma) and the body and tail length, distance from anterior end to excretory pore and to the base of pharynx of infective juveniles. The new species can also be distinguished from other Steinernema species by DNA sequences of either a partial 28S rDNA or the internal transcribed spacer (ITS) regions of rDNA, and from the closely related species S. longicaudum and S. guangdongense by cross-breeding tests.